An updated host-parasite catalogue of world Dryinidae (Hymenoptera: Chrysidoidea) - Guglielmino, Adalgisa; Olmi, Massimo; Bückle, Christoph (Zootaxa, 2013)
An updated host-parasite catalogue of world Dryinidae is presented. The catalogue presents 1014 relationships between dryinids and their hosts checked in 84 countries of the world, including 38 new records.